Structural and ultraviolet photo-detection properties of laser molecular beam epitaxy grown GaN layers using solid GaN and liquid Ga targets. (12th May 2021) - Mauraya, Amit Kumar; Mahana, Debashrita; Tyagi, Prashant; Ramesh, Ch; Shukla, Ajay Kumar; Husale, Sudhir; Kushvaha, Sunil Singh; Senthil Kumar, Muthusamy
Abstract: GaN epitaxial layers have been grown on sapphire (0001) substrate by laser molecular beam epitaxy technique using laser ablation of polycrystalline GaN solid and liquid Ga metal targets in the ambient of nitrogen plasma. In-situ reflection high energy electron diffraction and exsitu atomic force microscopy observations revealed that GaN growth using solid target yields rough surface under three-dimensional growth mode while a flat surface GaN is obtained using liquid Ga target. From X-ray rocking curve measurement, it is also observed that the GaN layer grown using solid GaN target has a relatively better structural quality. X-ray photoelectron spectroscopy confirmed Ga–N bond formation and near-stoichiometric composition of the GaN epilayers. The influence of threading dislocation density on the ultraviolet (UV) photoresponse properties of GaN layers have been studied using metal-semiconductor-metal (MSM) based device structure. It is found that the GaN MSM structure obtained using solid GaN target with lesser screw and dislocation densities exhibits a higher responsivity with fast response and recovery time.